Building beyond the visible a multi-sensory design approach on a neurodevelopmental disorder (NDD) therapy and rehabilitation center for children and adults - Guerrero, Phoebe Nicole A.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Living with an unnoticeable disability comes with everyday barriers that people do
not recognize. Neurodevelopmental disorders (NDDs) are lifelong complex disorders
related to brain development and functioning such as autism spectrum disorder
(ASD), attention-deficit hyperactivity disorder (ADHD), intellectual disability (ID),
communication disorders, specific learning disorders (SLDs), and motor disorders
(MDs) (American Psychiatric Association, 2013). The lack of facilities and support in
the Philippines and worldwide contribute to missed or late diagnosis. Rehabilitation
of these disorders commonly uses sensory integration theory, a therapeutic method
involving the regulation of sensory stimuli in the environment (Ayres, 1979) and
commonly requires ample space and equipment. In order to meet the growing
demands of people with NDDs across all ages and income groups, a designated
health facility is proposed as a venue to assist treatment with three main objectives:
an accessible and inclusive design, multidimensional and holistic interventions, and a
multi-sensory experience. To provide the foundations of the design proposal, a review
of existing literature was conducted alongside a series of semi-structured interviews
with healthcare professionals relevant to the management of NDDs. Gathered
information from the interview sessions were recorded and tabulated in relation to the
programmed spaces of the project. Through incorporating sensory integration with
multi-sensory design and other inclusive design criteria, the project aims to provide
effective treatment spaces tackling form, function, layout, circulation, lighting, and
acoustics. With the standalone NDD therapy and rehabilitation center for children
and adults, the project aims to create an outpatient health-focused environment
boosting the quality of life of the target population.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Rehabilitation centers; Sensorimotor integration; Health care facility